Solidifying Stress of ZL114A Alloy with Different Process Parameters - FENG Yi-cheng; ZHANG Ling-zhu; WANG Li-ping; MA Xu-liang; JIANG Wen-yong; GUO Er-jun; LIU Hong-hui; CHEN Dong-dong (Journal of Harbin University of Science and Technology)
The dynamic solidifying stress of ZL114A alloy was tested by stress testing equipment in this work.The effect of casting process parameters on solidifying stress of stress frame specimen was studied.The testing results show that the solidifying process has an important effect on the stress state and change of stress frame specimen with ZL114A alloy.The minimum stress value and final stress value of coarse bar in stress frame specimen increase with increasing of pouring temperature.The minimum stress value decreases and finial stress value increases with increasing of cooling rate.Compare to the specimen with unmodified treatment, the minimum stress value decreases and finial stress value increases for the modified ZL114A alloy with Sr